2008
DOI: 10.1002/cbic.200700436
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Analysis of Two Analytes in Solutions or on Surfaces by Using a Bifunctional Aptamer: Applications for Biosensing and Logic Gate Operations

Abstract: A bifunctional aptamer that includes two aptamer units for cocaine and adenosine 5'-monophosphate (AMP) is blocked by a nucleic acid to form a hybrid structure with two duplex regions. The blocked bifunctional aptamer assembly is used as a functional structure for the simultaneous sensing of cocaine or AMP. The blocked bifunctional aptamer is dissociated by either of the two analytes, and the readout of the separation of the sensing structure is accomplished by a colorimetric detection, by a released DNAzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 47 publications
0
86
0
Order By: Relevance
“…[5][6][7][8] For example, Elbaz et al reported an electrochemical method for the detection of cocaine and adenosine triphosphate (ATP) using a blocked bifunctional nucleic acid. [5] Yan et al developed an electrochemical biosensor for the detection of thrombin and adenosine using two bifunctional aptamers. [6] Nie et al fabricated a bifunctional aptamer-based electrochemical biosensor for the detection of ATP and lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] For example, Elbaz et al reported an electrochemical method for the detection of cocaine and adenosine triphosphate (ATP) using a blocked bifunctional nucleic acid. [5] Yan et al developed an electrochemical biosensor for the detection of thrombin and adenosine using two bifunctional aptamers. [6] Nie et al fabricated a bifunctional aptamer-based electrochemical biosensor for the detection of ATP and lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the biocatalytic nature of many utilized biomolecular processes, offers certain advantages for analog noise control in the binary-gate circuit design paradigm. [17] Proteins/enzymes [5][6][7][8][9][10][11][12][14][15][16][17][19][20][161][162][163][164][165] and DNA/RNA/DNAzymes [6,7,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] have been extensively used for gates, for realizing small networks and computational units, and for systems motivated [183] by applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various signal transduction methods, fluorescence has been the most often used due to its high sensitivity and versatility. 5,[20][21][22][23][24][25][26][27] In addition to intensity-based detection, fluorescence wavelength shift, anisotropy, lifetime, and energy transfer have all been reported for designing aptamer-based sensors. 5 Most fluorescent aptamer sensors involve cuvette-based measurements, in which the sensor and target analyte are mixed in a cuvette and the change of fluorescence signal is monitored with a fluorometer.…”
Section: Introductionmentioning
confidence: 99%